Efektivitas Teknik Mindfulness dalam Konseling Kelompok untuk Menurunkan Stres Akademik Mahasiswa Tingkat Akhir - Amalya, Naisatul; Wanty Khaira (JAMBURA Guidance and Counseling Journal, 2025)
Final-year university students often experience substantial academic stress due to the pressures of completing a thesis, managing supervisory dynamics, and meeting graduation requirements. This study examines the effectiveness of a mindfulness-based group counseling intervention in reducing academic stress among final-year students in the Guidance and Counseling Study Program. The research employed a one-group pretest–posttest design with seven purposively selected participants who exhibited moderate to high levels of academic stress. The intervention consisted of three group counseling sessions incorporating mindfulness techniques, including mindful breathing, STOP practice, cognitive–emotional observation, and guided reflection. Academic stress was measured using a validated and reliable stress scale. A paired-samples t-test revealed a significant decrease in stress scores from 87.60 (pretest) to 64.71 (posttest), t = 3.894, p = 0.008. These findings indicate that mindfulness-based group counseling effectively reduces academic stress and enhances emotional regulation in this sample. Practical implications suggest integrating mindfulness practices into university counseling services. The primary limitation is the small sample size; future research should employ larger samples and controlled experimental designs.